Physical Evaluation of Anti Acne Mask With Ethanol Extract of Purple Sweet Potato Leaf (Ipomoea batatas (L.) Antin-3 Varieties: Evaluasi Fisik Masker Anti Jerawat Dengan Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea batatas (L.) Varietas Antin-3 - Dipahayu, Damaranie; Lestari, Kinanti Ayu Puji (Journal of Pharmacy and Science, 2021)
Ethanol extract of purple sweet potato (Ipomoea batatas (L.)) leaves of Antin-3 variety contains flavonoids and polyphenols which can be used as a source of acne anti-bacterial because it can inhibit the growth of Staphylococcus aureus. This study aims to obtain data on physical characteristics, acceptability and stability of anti-acne mask formulation of 70% ethanol extract of Antin-3 leaves. The research method used were characteristic, acceptability and stability test. There were 4 types of samples tested, namely base, Antin-3 extract 5%: 10% and 20% (B: F1: F2: F3). The organoleptic results showed that the higher concentration of extract, the darker color of mask and the stronger of extract smell and the softer of consistency. The pH values ​​(B: F1:F2: F3) were respectively 6.46; 5.78; 5.75; 5.46. The value of adhesion (B: F1: F2: F3) were respectively 1.1; 1.46; 2.17 and 4.53 seconds. The value of spreading capacity (B: F1: F2: F3) were respectively 3.89; 4.15; 4.36 and 3.45 cm. The results of the acceptability test showed that F2 was the easiest formula to spread, clean and softest sensation on the skin. The results of the mechanical and cycling test showed that the four samples had not undergo phase separation. Anti-acne mask with 70% ethanol extract of Antin-3 leaves by 10% met the physical characteristics, acceptability and stability.